THE INFLUENCE OF INTRINSIC AND EXTRINSIC MOTIVATION ON STUDENT LEARNING ACHIEVEMENT WITH LEARNING MODELS (OFFLINE, ONLINE, AND HYBRID) AS MODERATING VARIABLE - Petradarmais, Yudha
Many factors can affect the student learning process, from internal student factors to external factors. Motivation is one of the components identified at the student internal factors that are linked and aimed to assure students' performance in the learning process. Learning model as external factors significantly affects students learning interest and the achievement of students’ understanding of the lecturer's material. However, during the pandemic, SBM ITB Undergraduate students experienced a decrease in learning motivation and the effectiveness of all learning model (online, offline and hybrid) remains underexplored. Regardless of the level of student motivation and the learning model implemented, students are still required to achieve optimal learning achievement. Therefore, to ensure student achievement remains optimal, this research is aimed to determine which learning model is the best and suitable to be applied in Undergraduate Program of SBM ITB and can help students increase their motivation and achievement in learning. This research will analyze the relationship between learning motivation (intrinsic and extrinsic) on student learning achievement and whether learning models (offline, online and hybrid) moderate the relationship between learning motivation and learning achievement. This research also analyzes the effectiveness of three learning model (offline, online and hybrid) based on student experiences and perception. This study is based on primary quantitative data. The data were collected through a well-structured questionnaire, and a total of 155 SBM ITB Undergraduate students answered the questionnaire. Research hypotheses were tested and analyzed using the multiple linear regression and moderated regression analysis method. From the results, learning motivation both intrnsic and extrinsic have positive relationship on learning achievement and learning model does not moderate the relationship between learning motivation and learning achievement. Based on the result analysis, the Undergraduate Program of SBM ITB does not need to be confused about the learning model to be chosen because there is no moderating effect given by the learning model on the relationship between learning motivation and learning achievement. Based on learning model effectiveness comparison, students had a more favorable experience and perception of offline learning compared to online learning and hybrid learning. Students prefer offline learning because it allows for more engagement and comprehension in the learning. Therefore, the researcher suggests that offline learning is the best and suitable learning model to be applicable in the Undergraduate Program of SBM ITB.